Comprehensive Analysis of Subtype-Specific Molecular Characteristics of Colon Cancer: Specific Genes, Driver Genes, Signaling Pathways, and Immunotherapy Responses - Hu, Fangjie; Wang, Jianyi; Zhang, Minghui; Wang, Shuoshuo; Zhao, Lingyu; Yang, Hao; Wu, Jinrong; Cui, Binbin (Frontiers in Cell and Developmental Biology, 2021)
Colon cancer is a complex, heterogeneous disease. The Colorectal Cancer Subtyping Consortium reported a novel classification system for colon cancer in 2015 to better understand the heterogeneity of colon cancer. Based on this molecular classification system, colon cancer was divided into four distinct consensus molecular subtypes (CMS 1, 2, 3, and 4). However, these subtype-specific molecular characteristics of colon cancer are largely unknown. In this study, 471 colon cancer samples from The Cancer Genome Atlas (TCGA) database were used for a multiomics analysis to explore the molecular characteristics of different colon cancer subtypes. We analyzed the alterations in subtype-specific gene expression and showed that particular subtype-specific genes significantly affected prognosis. We also explored the mutations and copy number variations (CNVs) of colon cancer driver genes and the representative genes of ten signaling pathways in different subtypes and revealed several genes that were altered in specific subtypes. Moreover, we detected the infiltration of various immune cells in different subtypes of colon cancer and showed that the infiltration levels of major immune cell types differed among these subtypes. Additionally, we explored changes in immune checkpoint genes and immunotherapy responses among different colon cancer subtypes. This study may provide insights into the molecular events contributing to carcinogenesis and development and provide potential markers and targets for the clinical diagnosis and treatment of different colon cancer subtypes.